Feeding Broiler Chickens with Grape Seed and Skin Meals to Enhance α- and γ-Tocopherol Content and Meat Oxidative Stability - Carlos Romero; Maria Nardoia; Ignacio Arija; Agustín Viveros; Ana I. Rey; Marin Prodanov; Susana Chamorro (MDPI AG, 2021)
Grape seeds (GS) and grape skins (GK) are natural sources of polyphenols with featured antioxidant capacity. An experiment was conducted to investigate the effect of these polyphenol sources in diets formulated to contain the same total extractable grape polyphenol content on growth performance, protein and extractable polyphenol digestibility, plasma and meat α- and γ-tocopherol and thigh meat oxidation in broiler chickens. Five experimental diets were formulated: control, control + vitamin E (200 mg/kg), 30 g/kg GS diet, 110 g/kg GK diet, GS + GK diet (a mixture of 24.4 g/kg GS and 13.1 g/kg GK designed to simulate a reconstituted grape pomace). Feeding chickens with 110 g/kg GK reduced (p < 0.001) daily weight gain, worsened (p < 0.001) feed conversion ratio, increased (p < 0.001) non-extractable polyphenol content in the ileum and in the excreta and decreased (p < 0.05) ileal protein digestibility. Regardless of the grape polyphenol source used, the inclusion of grape byproducts in the diets led to an increase of total extractable polyphenol contents in the ileum (p < 0.01) and the excreta (p < 0.001), which resulted (p < 0.001) in a decrease of extractable polyphenol digestibilities. Alpha- and gamma-tocopherol concentrations increased (p < 0.001) in plasma and in seven-day stored meat in birds fed the diet combining GS and GK with respect to the control group. As it happened with the vitamin E supplementation, feeding the combination of GS and GK also reduced (p < 0.001) the concentration of the lipid peroxidation marker (malondialdehyde) in the stored meat of chickens.